1980
DOI: 10.1111/j.1365-2125.1980.tb05826.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cimetidine on the absorption of orally administered tetracycline.

Abstract: 1 Six healthy female subjects received orally two 250 mg tetracycline tablets either with 400 mg cimetidine or placebo. In a separate experiment six healthy female volunteers received 500 mg tetracycline as a suspension on the fifth day of a 6 day regime of 400 mg cimetidine or placebo, 8 hourly and at bedtime. 500 mg tetracycline as tablets was also given with cimetidine only. 2 Following a single dose of cimetidine the mean peak tetracycline plasma concentration was significantly reduced by 1.2 microgram/ml … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1980
1980
1986
1986

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In the same study design as that described for ampicillin (section 1.4), the subjects took co-trimoxazole (160mg trimethoprim plus 800mg sulphamethoxazole) with and without cimetidine (Rogers et al, 1980). Again, no significant differences in the pharmacokinetics of sulphamethoxazole or trimethoprim were observed, although plasma concentrations of the latter tended to be higher under cimetidine treatment.…”
Section: Co-trimoxazolementioning
confidence: 87%
See 2 more Smart Citations
“…In the same study design as that described for ampicillin (section 1.4), the subjects took co-trimoxazole (160mg trimethoprim plus 800mg sulphamethoxazole) with and without cimetidine (Rogers et al, 1980). Again, no significant differences in the pharmacokinetics of sulphamethoxazole or trimethoprim were observed, although plasma concentrations of the latter tended to be higher under cimetidine treatment.…”
Section: Co-trimoxazolementioning
confidence: 87%
“…In I study a 400mg dose of cimetidine reduced the absorption of tetracycline (as measured by the area under the plasma concentration-time curve, and urinary excretion) by between 30 and 40 %. However, chronic dosing with cimetidine for 5 days had no effect on tetracycline disposition (Fisher et al, 1980). In another study, chronic treatment with cimetidine reduced the absorption of tetracycline (as measured by urinary excretion) from a capsule formulation by an average of 30 %, but had no effect when tetracycline was given in solution form (Cole et al, 1980).…”
Section: Tetracyclinementioning
confidence: 98%
See 1 more Smart Citation
“…Morrison et al (1980) found that although the coating should be soluble at pH 5 to 7, the bioavailabilty of prednisolone from an enteric-coated formulation was not affected by cimetidine under circumstances similar to those in which both drugs would be used by patients. Fisher et al (1980) found reduced absorption of tetracycline with singles dose administration, but Garty & Hurwitz (1980) did not find this with chronic administration. To complicate matters, Breckenridge et al (1979) found that cimetidine increased the action of warfarin in man by inhibition of drug metabolism.…”
Section: Discussionmentioning
confidence: 87%
“…We have, however, failed to demonstrate a clinically significant effect on the absorption of orally administered tetracycline (Fisher, House, Inns, Morrison, Rogers & Bradbrook, 1980). A preliminary report by Sternberg, King & Toskes (1978) has described inhibition of the absorption of Concurrent administration of food does not affect the absorption of enteric-coated prednisolone (Lee, Taylor, Walker & James, 1979).…”
Section: Concurrent Administration Of Cimetidine and Enteric-coated Pmentioning
confidence: 78%